2018
DOI: 10.1371/journal.pntd.0006227
|View full text |Cite
|
Sign up to set email alerts
|

The impact of insecticide applications on the dynamics of resistance: The case of four Aedes aegypti populations from different Brazilian regions

Abstract: BackgroundIn the tropics, the utilization of insecticides is still an important strategy for controlling Aedes aegypti, the principle vector of dengue, chikungunya and Zika viruses. However, increasing insecticide resistance in Ae. aegypti populations might hinder insecticide efficacy on a long-term basis. It will be important to understand the dynamics and evolution of insecticide resistance by assessing its frequency and the mechanisms by which it occurs.Methodology/Principal findingsThe insecticide resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 46 publications
4
68
0
6
Order By: Relevance
“…We also hypothesized that KDR‐type mutation is likely a prevalent mechanism leading to cross‐resistance between DDT and pyrethroids. This is because these compounds share the same mode of action and altered target site resistance was frequently reported in the region . Our results confirmed the expectation of widespread insecticide resistance in mosquito populations in Latin America and the Caribbean, particularly for the most commonly used insecticides.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also hypothesized that KDR‐type mutation is likely a prevalent mechanism leading to cross‐resistance between DDT and pyrethroids. This is because these compounds share the same mode of action and altered target site resistance was frequently reported in the region . Our results confirmed the expectation of widespread insecticide resistance in mosquito populations in Latin America and the Caribbean, particularly for the most commonly used insecticides.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of effective vaccines or pharmaceutical treatments for many of these neglected diseases places mosquito vector control in the forefront of the preventive initiatives against these maladies . Vector control, however, is no easy task and is achieved mainly through the use and overuse of insecticides against mosquito larvae and/or adults favoring the frequent development of insecticide resistance in the targeted insect populations …”
Section: Introductionmentioning
confidence: 99%
“…In Campo Grande, the highest RR values (above 50 for deltamethrin) revealed that the period with the highest incidence of dengue coincides with the detection of Ae. aegypti populations with high resistance 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In America, kdr mutations have been reported in Ae. aegypti populations from Ecuador, (22), United States (23, 24), Colombia (25, 26), México (2729), Brazil (3035), Lesser Antilles (3640), French Guiana (37), Venezuela (29, 41), Cuba (29, 39), Panamá (42), Puerto Rico (43). This is the first report of kdr mutations for the countries included in this study, except for Haiti (87).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to pyrethroids in mosquitoes have been widely associated with the F1534C (21, 23, 25, 27, 29, 30, 32, 3941, 83, 88101) and V1016I mutations (24, 25, 27, 29, 30, 32, 36, 38, 40, 41, 88, 93, 97, 100, 102, 103). The simultaneous presence of both mutations has been associated with enhanced tolerance to deltamethrin in the past (31).…”
Section: Discussionmentioning
confidence: 99%